PELAKSANAAN IKRAR WAKAF TANAH DAN PENDAFTARANNYA DI KUA KECAMATAN SUSUKAN DAN ATR/BPN KABUPATEN CIREBON - Wahid, Abdul; Rohadi, Rohadi (PROSIDING SENANTIAS: Seminar Nasional Hasil Penelitian dan Pengabdian kepada Masyarakat, 2021)
The phenomenon of waqf land application in Susukan District, Cirebon Regency is carried out individually and only based on religious principles between administrators. This is the basis if the waqf land does not yet have regulations, which will trigger the transfer of the waqf land or the issuance of an irresponsible subpoena. The purpose of this research is to record knowledge related to how the waqf pledge application process is carried out in the affairs of the Susukan District Religious Office and waqf land certificates at the ATR / BPN Office of Cirebon Regency. This approach method is a juridical reality that is carried out by looking at the phenomena contained in the practice in the field. The results of this study indicate that the Directorate General of Islamic Guidance, Ministry of Religion, Cirebon Regency, took solutions and strategic steps with ATR/BPN Kab. Cirebon in the framework of land waqf certification services. This step is a manifestation of the seriousness of the Ministry of Religion Kab. Cirebon responded in terms of land waqf to obtain authentic evidence from ATR/BPN Kab. Cirebon in the form of land waqf certificates. The application for the management of waqf land certificates can be carried out by the Prona program with an easy procedure, the legality of waqf land parcels can be owned by the community.